Enhancing Crop Productivity and Soil Health from Intercropping Coriander with Autumn Sugarcane through Scheduling of Fertilizer and Irrigation - and Vipin Kumar, Navnit Kumar, Geeta Kumari (Journal of the Indian Society of Soil Science, 2017)
The present investigation was carried out during autumn seasons of 2010-13 to find out the suitable fertility level and irrigation schedule for coriander (Coriandrum sativum L.) grown under sugarcane (Saccharum spp. hybrid complex) + coriander intercropping system on a recent alluvial soil (Entisol) of Bihar. The maximum cane yield (90.1 t ha-1) was recorded with sole sugarcane as compared to intercropping system. Yield of intercropped sugarcane decreased by 8.9 per cent over sole sugarcane. The results indicated that cane yield was significantly higher under F1 as compared to F3 but statistically similar to rest of the treatments. Application of 100% RDF to both the crops with residue incorporation (F1) recorded significantly higher grain (1.38 t ha-1), haulm (1.95 t ha-1) and biomass yield (3.33 t ha-1) of coriander over rest of the treatments. The 100% RDF to both the crops with residue incorporation (F1) showed higher N, P and K uptake. The post-harvest available N, P and K status and soil nutrient balance improved with the application of 100% RDF to both the crops and residue incorporation (F1). Among irrigation schedule, application of 2 irrigations at 60 and 90 DAS (I3) produced significantly higher yield of sugarcane (88.4 t ha-1) and grain (1.44 t ha-1), haulm (2.06 t ha-1), biomass yield (3.49 t ha-1) of coriander. Nutrient uptake by crop was also higher with higher level of irrigation.